Interpreting Revelation with Roman Coins: A Test Case, Revelation 6:9–11 - May, David M. (Review and expositor, 2009)
The altar scene in Revelation 6:9–11 has been interpreted as a positive image of martyred saints being presence with God in heaven. This article, however, challenges this traditional assumption. Based on Roman imperial coinage, especially those coins with images of altars, it is likely that John portrayed the altar in his narrative as not representing the heavenly altar of God but the imperial altar of Rome. John takes well-known Roman images and challenges his readers to resist the temptation these altars represent as symbols of the false ideology espoused by Rome. He also illustrates how these altars, like the cross of Christ, may become the symbol for his readers' martyrdom. This article also suggests that architectural images of altars on Roman coins can provide a way to understand the strange position of the martyred ones who are “under the altar.”